Insights on the trafficking and retro-translocation of glycosphingolipid-binding bacterial toxins - Cho, Jin A.; Chinnapen, Daniel J.; Aamar, Emil; te Welscher, Yvonne M.; Lencer, Wayne; Massol, Ramiro (Frontiers in Cellular and Infection Microbiology, 2012)
Some bacterial toxins and viruses have evolved the capacity to bind mammalian glycosphingolipids to gain access to the cell interior, where they can co-opt the endogenous mechanisms of cellular trafficking and protein translocation machinery to cause toxicity. Cholera toxin (CT) is one of the best-studied examples, and is the virulence factor responsible for massive secretory diarrhea seen in cholera. CT enters host cells by binding to monosialotetrahexosylganglioside (GM1 gangliosides) at the plasma membrane where it is transported retrograde through the trans-Golgi network (TGN) into the endoplasmic reticulum (ER). In the ER, a portion of CT, the CT-A1 polypeptide, is unfolded and then “retro-translocated” to the cytosol by hijacking components of the ER associated degradation pathway (ERAD) for misfolded proteins. CT-A1 rapidly refolds in the cytosol, thus avoiding degradation by the proteasome and inducing toxicity. Here, we highlight recent advances in our understanding of how the bacterial AB5 toxins induce disease. We highlight the molecular mechanisms by which these toxins use glycosphingolipid to traffic within cells, with special attention to how the cell senses and sorts the lipid receptors. We also discuss several new studies that address the mechanisms of toxin unfolding in the ER and the mechanisms of CT A1-chain retro-translocation to the cytosol.